Pharmacokinetics and tolerability of the dual TORC1/2 inhibitor sapanisertib in combination with the MEK inhibitor trametinib in dogs - Wei, Bih-Rong; Peer, Cody J.; Richardson, William J.; Hewitt, Stephen M.; Figg, William D.; Simpson, R. Mark (Frontiers in Veterinary Science, 2022)
Activation of one or both the Ras/MAPK and PI3K/Akt/mTOR signal transduction pathways are known to mediate oncogenicity of several canine and human cancers, including mucosal melanomas. Reciprocal cross activation between the two pathways can be a source of drug resistance. Consequently, oral dosing for plasma pharmacokinetic (PK) analysis and tolerability to a combination of sapanisertib, a dual TORC1/2 inhibitor, and trametinib, a MEK inhibitor, was evaluated in nontumor-bearing laboratory dogs for its potential application in parallel pathway targeting. Twelve dogs, divided into three equal cohorts, received either the combination or single agents. Animals were monitored for PK following single dose and 17-day repeat dosing, and by clinical observations, hematology, serum biochemistry, coagulation studies and urinalyses. A single trametinib dose (0.025mg/kg), sulfated as dimethyl sulfoxide which enhanced its absorption, reached mean maximum concentration (Cmax) 0.64 ng/mL (18% coefficient of variation (CV)) at a median time to maximum concentration (Tmax) of 1.5 hours (hr), and mean area under the concentration-time curve (AUC) 16.8 hr*ng/mL (14%CV)], which were similar when given alone or in combination with sapanisertib. A prolonged half-life afforded 3–4-fold plasma accumulation of trametinib with daily dosing, analogous to humans. Trametinib PK mirrored previous regulatory data in dogs, while exposure approximated some published human values but generally not all patients. Sapanisertib-alone in canine plasma following single 0.1 mg/kg dose (mean Cmax 26.3 ng/mL (21%CV), median Tmax 2.0 hr, and mean AUC 248 hr*ng/mL (41%CV)) resembled levels in human therapeutic trials; whereas canine sapanisertib exposure was reduced when combined with trametinib, a known cytochrome P450 CYP3A4 inducer. Sex differences were not observed for either drug. Side effects upon repeat dosing with either or both drugs may include body weight loss, maldigestion, and cutaneous discoloration. The combination was tolerated without dose limiting toxicity, although clinical laboratory analyses revealed drug-induced acute-phase inflammation, proteinuria, and decreased blood reticulocytes, mild changes not necessitating intervention. Short-term results in dogs with this combination would appear to hold translational promise for clinical trial evaluation to target canine and possibly human melanoma, as well as other cancers having one or both signal transduction pathway activations.